A case of nickel allergy after endovascular aortic repair. (February 2019) - Kawatani, Yohei; Kurobe, Hirotsugu; Nakamura, Yoshitsugu; Hori, Takaki
A 78-year-old man with no history of allergy, underwent endovascular aortic repair for abdominal aortic aneurysm rupture. Postoperatively, he had low-grade fever and persistently raised white blood cell counts, but tests showed no infection. A skin rash appeared on the trunk and upper arms; we suspected a drug allergy. Despite withdrawal and/or change of medications, the symptoms remained. Finally, a patch test for nickel showed a strongly positive result. Oral prednisone 5 mg·day −1 was started, and the clinical findings resolved thereafter. No recurrence of allergy, infection, or exacerbation of the treated abdominal aortic aneurysm was noted at the 2-year follow-up.